1997
DOI: 10.1006/dbio.1996.8455
|View full text |Cite
|
Sign up to set email alerts
|

Two Isoforms of Orthodenticle-Related Proteins (HpOtx) Bind to the Enhancer Element of Sea Urchin Arylsulfatase Gene

Abstract: The sea urchin (Hemicentrotus pulcherrimus) arylsulfatase (HpArs) gene, expressed specifically in aboral ectoderm, contains a 229-bp enhancer in its first intron that is required for the activation of HpArs gene expression. Deletion analysis shows that a tandem repeat of orthodenticle-related protein (Otx) binding sites are responsible for the activity of this enhancer. Gel mobility shift analysis reveals that three types of Otx-proteins, which show different mobilities in gel shift assays, form complexes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 0 publications
4
38
0
Order By: Relevance
“…HpArs (Sakamoto et al, 1997;Kiyama et al, 1998), Spec2a (Gan et al, 1995) and Endo16 (Yuh et al, 1998) have been reported as direct target genes of Otx in sea urchin embryo. HpArs is transcriptionally activated late in blastula, and after the gastrula stage it is expressed exclusively in the aboral ectoderm throughout embryonic development (Sasaki et al, 1988;Akasaka et al, 1990aAkasaka et al, , 1990b.…”
Section: Otx Target Genementioning
confidence: 99%
See 4 more Smart Citations
“…HpArs (Sakamoto et al, 1997;Kiyama et al, 1998), Spec2a (Gan et al, 1995) and Endo16 (Yuh et al, 1998) have been reported as direct target genes of Otx in sea urchin embryo. HpArs is transcriptionally activated late in blastula, and after the gastrula stage it is expressed exclusively in the aboral ectoderm throughout embryonic development (Sasaki et al, 1988;Akasaka et al, 1990aAkasaka et al, , 1990b.…”
Section: Otx Target Genementioning
confidence: 99%
“…In zebrafish three types of Otx are present in the developing diencephalon and midbrain (Mori et al, 1994). In sea urchin development, two isoforms of Otx are expressed (Mao et al, 1994;Sakamoto et al, 1997). The first type of Otx protein, referred to as an early-type Otx (HpOtxE), appears in early development and gradually decreases in amount by the gastrula stage.…”
Section: Otx Is Involved In Various Aspects In Sea Urchin Developmentmentioning
confidence: 99%
See 3 more Smart Citations